ANALISA DETERMINASI KINERJA KARYAWAN PADA PT BKK JATENG DI KABUPATEN WONOGIRI - Cahya Wulan Febriantari; Arif Nugroho Rachman (Juremi: Jurnal Riset Ekonomi, 2023)
This observation clearly aims to see the effect of the effectiveness of the application of accounting information systems, task suitability, work environment, and work motivation on the performance of PT BKK Central Java in Wonogiri Regency.Researchers used quantitative research methods. The number of population used is 135 employees with a sample using Roscoe theory, totaling 50 employees who are users of accounting information systems. Using primary data, namely by giving questionnaires to respondents with a Likert scale. Meanwhile, multiple linear regression analysis is the data analysis used.Based on the results of the research conducted, it is shown that negatively the effectiveness of the application of accounting information systems, task suitability and work environment have a negative effect on employee performance, while work motivation has a positive effect on employee performance.